Productivity Convergence : Theory and Evidence - Wolff, Edward N. (Cambridge : Cambridge University Press, 2013)
A vast new literature on the sources of economic growth has now accumulated. This book critically reviews the most significant works in this field and summarizes what is known today about the sources of economic growth. The first part discusses the most important theoretical models that have been used in modern growth theory as well as methodological issues in productivity measurement. The second part examines the long-term record on productivity among Organization for Economic Co-operation and Development (OECD) countries, considers the sources of growth among them with particular attention to the role of education, investigates convergence at the industry level among them, and examines the productivity slowdown of the 1970s. The third part looks at the sources of growth among non-OECD countries. Each chapter emphasizes the factors that appear to be most important in explaining growth performance.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Production (Economic theory); Endogenous growth (Economics); Industrial productivity